Including cultural water requirements in environmental flow assessment: an example from the upper Ganga river, India - Lokgariwar, C.; Chopra, R.; Smakhtin, Vladimir U.; Bharati, Luna; O'Keeffe, J. (Informa UK Limited, 2014)
The rituals of riparian communities are frequently linked to the flow regimes of their river. These dependencies need to be identified, quantified and communicated to policy makers who manage river flows. This paper describes the first attempt to explicitly evaluate the flows required to maintain the cultural and spiritual activities in the upper Ganga River basin. Riparian dwellers and visitors were interviewed and the responses analyzed to obtain an overview of the needs and motivations for cultural flows. The approach enhances the overall concept of environmental flow assessment, especially in river basins where spiritual values ascribed to rivers are high.